2018
DOI: 10.18388/abp.2018_2609
|View full text |Cite
|
Sign up to set email alerts
|

The role of eicosanoids in renal diseases – potential therapeutic possibilities

Abstract: Eicosanoids are biologically active molecules that are created in the process of oxidation of arachidonic acid (AA) which is a constituent of the cell membrane phospholipids. Throughout the years it was evidenced by experiments that the lipid and lipid-derived metabolites play an important role in physiological and pathological processes in the kidneys. They are being considered as biomarkers in detecting acute kidney injury, nephrotoxicity, glomerulonephritis and early stages of diabetic nephropathy because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…A Bar chart of the top 30 significant GO terms from the targets. B-E GOChord to donate the relationship between GO terms and potential targets which are related to immunomodulatory and inflammatory effects membrane phospholipids, is being considered biomarkers for detecting acute kidney injury, nephrotoxicity, glomerulonephritis, and early stages of diabetic nephropathy because of their participation in inflammatory processes and in oxidative stress (Fijalkowski et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A Bar chart of the top 30 significant GO terms from the targets. B-E GOChord to donate the relationship between GO terms and potential targets which are related to immunomodulatory and inflammatory effects membrane phospholipids, is being considered biomarkers for detecting acute kidney injury, nephrotoxicity, glomerulonephritis, and early stages of diabetic nephropathy because of their participation in inflammatory processes and in oxidative stress (Fijalkowski et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the enriched gene sets in this study have been suggested to mediate renal dysfunction. Eicosanoids and arachidonic metabolism play major roles in kidney inflammation and have been shown to predict chronic kidney disease progression in patients [ 44 , 45 , 46 ]. Extracellular matrix turnover plays a role in aberrant wound healing and fibrosis, which is a hallmark of kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, experiments have indicated that lipids and lipid-derived metabolites were not only involved in inflammatory processes and oxidative stress but also played an important role in the physiological and pathological processes of the kidney. Arachidonic acid (AA) is a component of cell membrane phospholipids, which makes us believe that its connection to the kidney is also related to the improvement of inflammation and reduction of oxidative stress [24]. Studies have found out that low linolenic and linoleic acid consumption are associated with the chronic kidney disease in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%